Differing Modes of Biotic Connectivity within Freshwater Ecosystem Mosaics - Mushet, David M.; Alexander, Laurie C.; Bennett, Micah; Schofield, Kate; Christensen, Jay R.; Ali, Genevieve; Pollard, Amina; Fritz, Ken; Lang, Megan W. (JAWRA Journal of the American Water Resources Association, 2019)
Abstract We describe a collection of aquatic and wetland habitats in an inland landscape, and their occurrence within a terrestrial matrix, as a “freshwater ecosystem mosaic” (FEM). Aquatic and wetland habitats in any FEM can vary widely, from permanently ponded lakes, to ephemerally ponded wetlands, to groundwater‐fed springs, to flowing rivers and streams. The terrestrial matrix can also vary, including in its influence on flows of energy, materials, and organisms among ecosystems. Biota occurring in a specific region are adapted to the unique opportunities and challenges presented by spatial and temporal patterns of habitat types inherent to each FEM. To persist in any given landscape, most species move to recolonize habitats and maintain mixtures of genetic materials. Species also connect habitats through time if they possess needed morphological, physiological, or behavioral traits to persist in a habitat through periods of unfavorable environmental conditions. By examining key spatial and temporal patterns underlying FEMs, and species‐specific adaptations to these patterns, a better understanding of the structural and functional connectivity of a landscape can be obtained. Fully including aquatic, wetland, and terrestrial habitats in FEMs facilitates adoption of the next generation of individual‐based models that integrate the principles of population, community, and ecosystem ecology. , Research Impact Statement : Fully including aquatic, wetland, and terrestrial habitats facilitates adoption of next‐generation, individual‐based, models that integrate principles of population, community, and ecosystem ecology.